BIODEGRADABLE FILMS PRODUCED WITH ORANGE PEEL AND REINFORCED BY BACTERIAL CELLULOSE - Alata Mayhuire, Evelin (2018)
This work proposes the formulation of biofilms out of orange peel, using pectin as a crosslinking agent and glycerol as plasticizer. Also, it was determined the impact of the addition of bacterial cellulose obtained from the static fermentation of kombucha (Manchurian fungus) in such biofilms. It is noticeable that the orange peel has been subject previously to an extraction process by steam distillation to recover its essential oil. Experimentally it was determined that an appropriate biofilm formulation has the following mass percentages: orange peel, 15; bacterial cellulose, 5; pectin, 40; and glycerol, 40. Such biofilm showed the following property values: tension stress at break, 5.53 N/mm2 ; elongation at break, 51.60 %; and, water vapor permeability, 0.0273 g.mm/(h.kPa.m2 ). Pectin content affected significantly the properties of the biofilms due to its interaction with glycerol. Bacterial cellulose contributed to increase the tension stress of the biofilm, but it reduced the value of elongation and water vapor permeability, which may be convenient for a diversity of applications. That is why bacterial cellulose constitutes an efficient reinforcing agent, whose production process is simple and safe.